Diseño del sistema de abastecimiento de agua potable y alcantarillado en el caserío de Caypanda, Distrito y Provincia de Santiago de Chuco. Región La Libertad - Carbajal Felipe, Wélinton Conrado (2009)
The work made on Design ofthe system ofpotable sewage system and water supply in the small village of Caypanda, allows to give a solution to the lack of cover of the services of potable water and sewage system, and coverall with the execution of this project will improve the conditions of life remarkably and of health of the community, specifically to the infectocontagiosas diseases that cause the morbidity and mortality will be reduced that affect to the settlers due to the deficiency of these services. The made hydraulic exposition rs for a countryside, of rough topography and dispersed population, has been made the microbiological analyses and physicalchemistries of the quality of the water of the springs the Jam (High Part) and the Cortadera (Low Part), have been made a hydrological study of the water sources (flowing) by a period of 1 O months to see the variability and availability of volumes of water during this time, has been taken into account the feasibility study considering the social, technical and sanitary aspect; and the hydraulic and structural calculation of each one of civil works. For the potable water supply, it will be used 02 slope pick up, lines of conduction with pipes PVC SAP C-7.5, 03 reservorios of concrete armed, networks of opened water distribution, 18 cameras it breaks domiciliary pressure and 119 sinks; and for the sewage system 119 sanitary latrines of the type ventilated dry hole will be constructed. The system of water supply is a system by gravity without treatment with a period of design of 20 years, and the sewage system is with sanitary latrines of dry processes with a period of design of 10 years.